Measurement of the Wingbeart Frequency of the Aedes aegypti PROVENIENTS FROM A REGION OF VENEZUELA (Revista Venezolana de Salud Pública, 2018)
In order to develop intelligent traps as vector control mechanisms for the prevention and reduction of metaxenic diseases, a physiological parameter is determined as the wingbeat frequency used for later characterization by genus of the Aedes aegypti mosquito in Venezuelan strains. For this, acoustic records were made with wild samples collected in rainwater reservoirs and emerged under controlled conditions in the laboratory. The recordings were made during one minute, in more than a hundred mosquitoes of this species and in both sexes, using a particle speed microphone connected to the audio input of a portable computer and a specialized program for acoustic records. A spectral analysis of the samples was carried out, determining that the average fundamental frequency of flutter for females corresponded to 454.78 ± 55.19 Hz and for males 688.39 ± 40.82 Hz, concluding that the groups were very separated in Its fundamental frequency, with which this parameter is a characteristic that can be used for the detection and classification of mosquitoes of this species, using artificial intelligence in capture devices for vector monitoring and control.
Keywords: Aedes; wingbeat; vector; Venezuela; NaWarao